Geometridae (Lepidoptera) of the Baikal region: keys to species and an annotated catalogue. Part 1. Ennominae - Makhov, Ilya (Zootaxa, 2021)
The dichotomous keys to 106 species from 62 genera of Ennominae (Lepidoptera: Geometridae) of the Baikal region (Irkutskaya Oblast and Buryatia, Russia) is given. The annotated catalogue including synonyms, the details of examined specimens, data on distribution and hostplants with references is provided. Distribution of Macaria artesiaria ([Denis et Schiffermüller], 1775) in the Baikal region is confirmed. One species is newly combined with genus Hypoxystis Prout, 1915: H. reticulata (Sterneck, 1928) comb. nov. The genus name Scardostrenia Sterneck, 1928 is established to be a synonym of Hypoxystis Prout, 1915 syn. n. Some taxonomic aspects of Charissa turfosaria (Wehrli, 1922), Hypoxystis reticulata (Sterneck, 1928), Synopsia strictaria Lederer, 1853 and Autotrichia heterogynoides (Wehrli, 1927) are discussed. New westernmost boundary of the range of Abraxas karafutonis Matsumura, 1925 is established.